Turkey - Country Economic Memorandum : Towards Macroeconomic Stability and Sustained Growth, Volume 3. Statistical Annex - World Bank (Washington, DC, 2013)
This report addresses key questions facing Turkish policymakers: how to sustain the economic recovery that began in 2002 following the deep crisis of 2001, how to ensure disinflation and public debt sustainability, and how to foster broad-based and equitably distributed growth in the future. After a brief review of the 2001 crisis and the Government response, the report analyzes the economic opportunities and challenges facing Turkey, and identifies policies to build on the economic recovery which began in 2002. The CEM develops a comprehensive four-point agenda for sustainable and more equitably distributed growth. The agenda encompasses: (i) macroeconomic stability, (ii) effective government, (iii) improved business environment, and (iv) stronger social policies. The report closes with medium-term macroeconomic projections to illustrate Turkey's prospects under a scenario of sustained reform and to highlight the risks to growth and macroeconomic stability should the economic program go off track.